(untitled) (Journal of actual problems of jurisprudence, 2019)
The author article "To problem of completion of the crimes on rail-freight traffics" author lit most sharp problems, appearing in the course of reluctances to criminal manifestations in considered direction, as well as are given offers on optimization of preventive activity.